Various aspects of ultrasound assisted emulsion polymerization process - Korkut, Ibrahim; Bayramoglu, Mahmut (Elsevier Science Bv, 2014)
In this paper, the effects of ultrasonic (US) power, pulse ratio, probe area and recipe composition were investigated on two process responses namely, monomer (methyl methacrylate, MMA) conversion and electrical energy consumption per mass of product polymer (PMMA). Pulsed mode US is more suitable than continuous mode US for emulsion polymerization. The probe (tip) area has little effect on the yield of polymerization when comparing 19 and 13 mm probes, 13 mm probe performing slightly better for high conversion levels. Meanwhile, large probe area is beneficial for high conversion efficiency of electric energy to US energy as well as for high radical generation yield per energy consumed. The conversion increased slightly and electrical energy consumption decreased substantially by using a recipe with high SDS and monomer concentrations. Conclusions presented in this paper may be useful for scale-up of US assisted emulsion polymerization. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Emulsion polymerization; PMMA; Probe area; Pulse ratio; Ultrasound efficiency